PENGARUH PENDIDIKAN KESEHATAN DALAM PELAKSANAAN HOME CARE TERHADAP KEMANDIRIAN ACTIVITY DAYLY LIVING (ADL) PENDERITA STROKE DI WATAMPONE - Zaenal; Rini Mustamin (Stikes Graha Edukasi Makassar, 2022)
The purpose of the study was to determine the effect of health education in the implementation of home care on the independence of Activity Daily Living (ADL) of stroke patients in Watampone. Research Methods. The research design used in this study was a pre-experimental method with one group pretest-posttest design, namely research that used one group of subjects, measurements were carried out before and after giving treatment to the subject. This research uses non-probability sampling with purposive sampling method. The results of the statistical test showed that there was an effect of health education on the independence of Activity Daily Living (ADL) with a value of p=0.005, attitude (affective) in terms of Activity Daily Living (ADL) with a value of p=0.008, action/practice (psicomotor) in terms of activity Daily Living (ADL) with p value = 0.046, Discussion. Knowledge ability (Cognitive) Activity Daily Living (ADL) can be improved by introducing stroke sufferers about their condition, knowledge of goals, tools and equipment, procedures for meeting the needs of Activity Daily Living (ADL) in order to maintain the fulfillment of needs, improve the quality of life. Attitude (affective) ability of Activity Daily Living (ADL) can be improved by health education by motivating stroke patients to prepare tools and equipment to meet the needs of Activity Daily Living (ADL) in order to maintain the fulfillment of their needs independently. The role of health education is rehabilitation. Suggestions for nurses who do home care should provide health education about the independence of Daily Living Activities (ADL) in stroke patients on a wider, sustainable scale to increase the independence of stroke sufferers